Vitamin E and peroxidation of Paring oil and coconut oil - Hayag, Miraluna S.; Lim-Sylianco, Clara Y. (Quezon City Department of Chemistry, College of Arts and Sciences, University of the Philippines Diliman, 1967)
Unsaturated fatty acids in the mitochondria undergo peroxidation, giving rise to lipide free radicals and peroxides, and subsequently resulting to the deterioration of this cell component. To gather evidence of lipide peroxidation, its occurrence in the isolated mitochondria of rat livers mixed with coconut oil and paring oil, with or without the addition of vitamin E, was studied. The color reaction of the resulting lipide peroxides with thiobarbituric acid (TBA) made possible the products' colorimetric determination and direct measurement as TBA reactants. The isolated mitochondria with paring oil produced more TBA reactants than that with coconut oil. In both cases, however, the addition of vitamin E resulted to a decrease in the peroxide formation. Thus, these results indicate that vitamin E functions as an important lipide antioxidant in the protection of the mitochondria.
Thesis (Bachelor of Science in Chemistry)--University of the Philippines Diliman, May 1967.
Keywords: Vitamin E; Coconut oil; Coconut; Peroxidation